Complete Sonatas for Pianoforte: Critical Commentary - Del Mar, Jonathan (Kassel Bärenreiter, 2020)
Alongside the Urtext edition of Beethoven’s 35 piano sonatas which sets new standards for the 21st century, world-renowned Beethoven expert Jonathan Del Mar presents a Critical Commentary to this body of works.With diligence and factual accuracy, he documents readings and editorial decisions, discusses problematic sections and provides answers for questions that have occupied and divided scholars for decades, including Beethoven’s notational idiosyncrasies and particular issues relating to performance practice. The Critical Commentary is more than a mere list of findings: It is a fascinating read offering valuable glimpses into Beethoven’s compositional process. This scholarly contribution is unparalleled in its precision and indispensable for in-depth studies of Beethoven’s piano sonatas.
Signs and conventions -- Appendices -- Critical Commentary -- Sonatas in E-flat major, F minor, D major WoO 47 -- Sonatas in F minor, A major, C major op. 2 -- Sonata in E-flat major op. 7 -- Sonatas in C minor, F major, D major op. 10 -- Sonata in C minor op . 13 (Pathétique) -- Sonatas in E major, G major op. 14 -- Sonata in B-flat major op. 22 -- Sonata in A-flat major op. 26 -- Sonatas in E-flat major, C-sharp minor op. 27 -- Sonata in D major op. 28 -- Sonatas in G major, D minor, E-flat major op. 31 -- Sonatas in G minor, G major op. 49 -- Sonata in C major op. 53 -- Sonata in F major op. 54 -- Sonata in F minor op. 57 -- Sonata in F-sharp major op. 78 -- Sonata in G major op. 79 -- Sonata in E-flat major op. 81a (Lebewohl, Abwesenheit und Wiedersehn) -- Sonata in E minor op . 90 -- Sonata in A major op. 101 -- Sonata in B-flat major op. 106 -- Sonata in E major op. 109 -- Sonata in A-flat major op. 110 -- Sonata in C minor op . 111 -- Appendix 1: Suspected errors -- Appendix 2: Alternative readings -- Appendix 3: First movement: Differences between A1 and A2 -- Appendix 4: Authentic readings in later sources -- Bibliography
Keywords: Beethoven, Ludwig van -- 1770-1827; Sonata; Piano; Musical analysis